Variation of Moni Nakhah and Daśain - Shakya, Saraswati Rashmi (Historical Journal, 2023)
Moni Nakhah and Daśain fall during the same days in the lunar calendar, both bear equal importance and relevance in their respective cultural origins. The influence of Hinduization and Sanskritization that arose with the entry of several rulers in the Nepaa Maṇḍala caused momentum forcing the identity of the ones who celebrate it to be in crisis. Festivals like Moni and Daśain with varying cultural backgrounds have co-existed and should, rather than facing a transitional merger. Moni and Daśain are both unique festivals that snowballed into bearing some similarities with time. It is noteworthy that, nowadays, using the terms Daśain and Moni interchangeably does not appear to elicit any concerns. This article aims to elucidate the differences between these two festivals unveiling the influence of Sanskritization and Hinduization.